ĐA DẠNG CÂY THUỐC THUỘC NGÀNH NGỌC LAN (MAGNOLIOPHYTA) CÓ TIỀM NĂNG CHỮA BỆNH THẤP KHỚP TẠI KHU BẢO TỒN THIÊN NHIÊN KON CHƯ RĂNG, TỈNH GIA LAI - Trần, Đức Bình; Bùi, Hồng Quang; Trịnh, Ngọc Hiệp (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
DIVERSITY OF MEDICINAL PLANTS (MAGNOLIOPHYTA) USED TO TREAT RHEUMATISM IN KON CHU RANG NATURE REVERSE, GIA LAI PROVINCEOur survey in Kon Chu Rang Nature Reverse for investigation of medicinal plants of Magnoliophyta resulted 56 species belonging to 48 genera, 29 families, 2 classes which can be used to treat rheumatism. Magnoliopsida was found to be the most dominant class (48 species) with 85.7% and Liliopsida (8 species) with 14.3% of the total. The Rubiaceae was the most dominant family with 11 species (19.6% of all species). The Morinda genus was the most dominant genus with 3 species (5.4% of all species). There are 14 species of rare medicinal plants with potential to cure rheumatism in Kon Chu Rang Nature Reserve belong to the Vietnam Red Book (2007) and Decree No. 84/2021 NĐ-CP of the Vietnam Government and IUCN Red List (2022).